2012
DOI: 10.1371/journal.pone.0046712
|View full text |Cite
|
Sign up to set email alerts
|

Select Small Core Structure Carbamates Exhibit High Contact Toxicity to “Carbamate-Resistant” Strain Malaria Mosquitoes, Anopheles gambiae (Akron)

Abstract: Acetylcholinesterase (AChE) is a proven target for control of the malaria mosquito (Anopheles gambiae). Unfortunately, a single amino acid mutation (G119S) in An. gambiae AChE-1 (AgAChE) confers resistance to the AChE inhibitors currently approved by the World Health Organization for indoor residual spraying. In this report, we describe several carbamate inhibitors that potently inhibit G119S AgAChE and that are contact-toxic to carbamate-resistant An. gambiae. PCR-RFLP analysis was used to confirm that carbam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
69
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 30 publications
(73 citation statements)
references
References 57 publications
(88 reference statements)
3
69
1
Order By: Relevance
“…A later study used yeast cells to express the catalytic domains of both WT and G119S Ag AChE [22]. This study confirmed the high V max of WT Ag AChE (2,700 U/mg, cf.…”
Section: An Gambiae Acetylcholinesterasesupporting
confidence: 55%
See 4 more Smart Citations
“…A later study used yeast cells to express the catalytic domains of both WT and G119S Ag AChE [22]. This study confirmed the high V max of WT Ag AChE (2,700 U/mg, cf.…”
Section: An Gambiae Acetylcholinesterasesupporting
confidence: 55%
“…However, the measured k cat (7.4 × 10 3 min −1 ) of the WT Ag AChE enzyme was significantly lower than that obtained by other groups (cf. Table 2) [21,22]. Finally, transcript levels of ace -1 and ace -2 Ag AChE were studied in An.…”
Section: An Gambiae Acetylcholinesterasementioning
confidence: 99%
See 3 more Smart Citations